Biomimetic Liposome with Surface‐Bound Elastase for Enhanced Tumor Penetration and Chemo‐Immumotherapy. Issue 19 (23rd June 2021) - Li, Yong‐Jiang; Wu, Jun‐Yong; Hu, Xiong‐Bin; Ding, Tianjinhao; Tang, Tiantian; Xiang, Da‐Xiong
Abstract: Dense extracellular matrix (ECM) in the tumor stroma has been a challenge for drug penetration and cytotoxic T lymphocyte (CTL) infiltration. Neutrophil elastase (NE), in surface‐bound form, can destruct ECM rapidly, may be used for remodeling tumor ECM, and overcoming tumor stromal barrier. Focusing on elastosis in triple‐negative breast tumor, biomimetic liposomes with chimeric cell membrane proteins (LMP) are developed and for the first time, it is demonstrated that LMP with surface‐bound elastase (NE‐LMP) can target and degrade ECM effectively in tumor stroma, with minimal toxicity to normal tissues. The pretreatment of NE‐LMP increases the accumulation of chemotherapeutics at the tumor site and enhances antitumor effects. Also, NE‐LMP facilitates CTL infiltration in tumors and exhibits enhanced chemo‐immunotherapy in combination of PD‐1 immune checkpoint blockade treatment in orthotopic 4T1 tumor‐bearing mice, with significantly prolonged survival. Moreover, the remodeling of the tumor ECM by NE‐LMP shows inhibiting effects on metastasis in the lung. Findings from this study suggest that NE‐LMP holds promise for enhancing deep penetration of drug and infiltration of CTL in desmoplastic tumor by effective degrading ECM in the tumor stroma. Abstract : The dense ECM in stroma of triple‐negative breast tumors limits penetration of chemotherapeutics and infiltration of cytotoxic T lymphocytes into the tumor. In this study, biomimetic liposomes with membrane proteins and surface‐bound elastase (NE‐LMP) are developed for targeted remodeling of tumor ECM. The combined treatment of NE‐LMPs with chemotherapeutics and PD‐1 immune checkpoint blockade exhibit enhanced tumor chemo‐immunotherapy.